2012
DOI: 10.1007/s13758-012-0050-x
|View full text |Cite
|
Sign up to set email alerts
|

Three Dimensional Tracking of Exploratory Behavior of Barnacle Cyprids Using Stereoscopy

Abstract: Surface exploration is a key step in the colonization of surfaces by sessile marine biofoulers. As many biofouling organisms can delay settlement until a suitable surface is encountered, colonization can comprise surface exploration and intermittent swimming. As such, the process is best followed in three dimensions. Here we present a low-cost transportable stereoscopic system consisting of two consumer camcorders. We apply this novel apparatus to behavioral analysis of barnacle larvae (≈800 μm length) during … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

2
13
0
1

Year Published

2012
2012
2017
2017

Publication Types

Select...
5
1

Relationship

1
5

Authors

Journals

citations
Cited by 12 publications
(16 citation statements)
references
References 28 publications
2
13
0
1
Order By: Relevance
“…Surface interaction at similar velocities has been reported previously for highly hydrated surfaces ( polyethylene glycol) [26], hydrophilic surfaces and also for zwitterionic hydrated surfaces [10].…”
Section: Motion Patternssupporting
confidence: 84%
See 2 more Smart Citations
“…Surface interaction at similar velocities has been reported previously for highly hydrated surfaces ( polyethylene glycol) [26], hydrophilic surfaces and also for zwitterionic hydrated surfaces [10].…”
Section: Motion Patternssupporting
confidence: 84%
“…The stereoscopy set-up consisted of two synchronized consumer camcorders as described recently [26]. The cameras imaged the surface of interest from the top at a relative angle to each other of ca 808 and a distance to the water surface of ca 40 cm.…”
Section: Stereoscopic Three-dimensional Tracking and Measurement Procmentioning
confidence: 99%
See 1 more Smart Citation
“…Recent work showed that 3D tracking of cyprids provides more detailed information, since it allows a clear distinction between sinking and swimming phases (Fig. 11) [102]. The data reveals that positively charged surfaces seem to cause longer periods of close surface inspection of cyprids of the barnacle Semibalanus balanoides than glass or PEG.…”
Section: D Tracking Of Barnacle Cypridsmentioning
confidence: 79%
“…11 3D Trajectories of swimming and exploring cyprids of the barnacle Semibalanus balanoides close to a glass surface (reproduced from Ref. [102] (Fig. 5a, Ó Springer 2012) with kind permission from Springer Science and Business Media) electrostatic interactions between the footprint material and the negatively charged surfaces occur.…”
Section: Footprints Of Walking Cyprids Visualized By Imaging Surface mentioning
confidence: 99%